Quality of minas frescal cheese prepared from milk with different somatic cell counts - Andreatta, Evelise; Fernandes, Andrezza Maria; Santos, Marcos Veiga; Mussarelli, Camila; Marques, Marina Célia; Gigante, Mirna Lúcia; Oliveira, Carlos Augusto Fernandes de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effects of using bulk milk with different somatic cell counts (SCC) on the quality of minas frescal cheese. A randomized complete block design was used, with 3x5 factorial treatments, with three SCC levels (low, 125,000 cells mL-1; intermediate, 437,000 cells mL-1; and high, 1,053,000 cells mL-1) and five storage durations. Cheese was vacuum-packed in plastic bags and analyzed after 2, 9, 16, 23 and 30 days of storage at 4°C. Somatic cell counts did not affect dry matter, fat, ash content, pH, free fatty acid concentrations and sensory parameters of minas frescal cheese. However, SCC in milk increased losses of protein in whey and decreased the cheese protein content. These changes did not affect the moisture-adjusted cheese yield and proteolysis during 30 days of storage. An interaction effect between SCC and time of storage was observed for firmness and sensory grades of cheeses. Results indicated that raw milk used to produce minas frescal cheese should not contain high SCC, in order to avoid lower acceptance of the product after 30 days of storage.
Keywords: cheese quality; proteolysis; somatic cell count